Performan Produksi dan Kualitas Kuning Telur Ayam Ras yang Diberikan Pakan Fermentasi - Hari Permadi; Sahrul Gunadi (Biocaster : Jurnal Kajian Biologi, 2026)
This study aims to determine the effect of the application of fermented walking mill rice bran using Effective Microorganisms (EM4). The observed parameter is the quality of purebred chicken yolks. The research was carried out through three stages, namely the comparison of the nutritional quality of DPPB with factory bran, DPPB fermentation with three EM4 formulations, and the application of fermented DPPB in purebred chickens. The results showed that the nutritional content of DPPB was lower than the quality standards of factory bran, especially in the protein content. The fermentation process increased the protein content of DPPB by 1.2%. The application of fermented DPPB resulted in the highest protein content in the P4 treatment (13.2%), the highest fat content in the P3 treatment (5.6%), and the highest cholesterol content in the control treatment (56.2%). Thus, DPPB fermentation using EM4 has the potential to increase the nutritional value of bran as an alternative feed ingredient for purebred chickens.